Implementation of Life Skills for Children with Disabilities At SDN Dringu - Jannah, Faridahtul; Wardana, Ludfi Arya (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this research is to prepare children with disabilities academically, socially, and emotionally in facing difficulties and life problems that require them to have life skills so that they can be more independent and not rely on others and can stand on their own feet someday. The research was conducted through a qualitative approach, where the targets of this research were students with disabilities at SDN Dringu. There are several stages in the implementation of this life skill, the first is the introduction of the concept of life skills, then the second stage is to gain learning experience with the implementation of life skills and the last is the review of children with disabilities. The results showed that the implementation of life skills for students with disabilities there can be applied quite well by students there, as evidenced by our interviews with homeroom teachers and students, where the homeroom teacher felt this, 1-2 children began to show quite good behavioral changes despite the short duration of our research. besides that, students voluntarily help group friends who have difficulties, they have dared to interact with others, and the relationship between friends becomes closer. These reflective skills are seen as an important aspect of teachers' ability to flexibly adjust their teaching to make optimal choices in response to students' learning progress.